FACTORS AFFECTING THE QUALITY OF FINANCIAL STATEMENTS ON SMALL MEDIUM ENTERPRISES (SMES) IN PONTIANAK - B1034131010, Erwinsyah (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACT             The purpose of this study is to examine the factors that affect the quality of financial statements of SMEs on the amount of credit received by using several indicators, such as education level, education background, size of business, age of business and the influence of information and the socialization of SAK EMKM to the willingness of entrepreneurs in adopting SAK EMKM in their financial statements. Data is collected through the questionnaire distribution from 100 respondents who run their business in the city of Pontianak and also data collected through the questionnaire from 6 investors consisting of 5 banking institutions and 1 non-banking institution.             The results showed that Model 1 hypothesis on the education level and business size had an effect on the perceptions of entrepreneurs regarding the quality of financial statements in their businesses. Educational background and age of business had not positive influence on the perception of entrepreneurs regarding the quality of financial statements in their businesses. Model 2 hypothesis type of business and business size shows no effect on bank credit for MSMEs in Pontianak while the hypothesis of the quality of financial reports had an affects on bank credit received by MSMEs. Model 3 shows that the prospect of the willingness of MSMEs in applying the SAK EMKM to improving the quality of MSME financial statements hasn?t achieved optimally. Considering that the understanding of MSME entrepreneurs is still very low in the contents of the SAK EMKM. Keywords: Education level, Educational background, Business size, Age of business, Quality of financial statements, information and socialization of SAK EMKM. REFERENCES Auken, V., & Howard. (2017). Turkish SMEs? Use of Financial Statements for      Decision Making. Pepper Dine.Abrori, Agnesti Rizki.(2010). Faktor-faktro yang Mempengaruhi Kebutuhan Standar Akuntansi Keuangan (SAK) Bagi Usaha Kecil dan Menengah (UKM). Jawa timur : Skripsi. Baas, T., & Schrooten, M. (2005). Relationship Banking and SMEs A Theoretical Analysis. DIW Berlin.Basri, Zainul.Y & Nugroho. M (2009). Ekonomi Kerakyatan : Usaha Mikro, Kecil, dan Menengah. Jakarta : Penerbit Universitas Trisakti Bank Mandiri.Beest, F. v., Braam, G., & Boelens, S. (2009). Quality of Financial Reporting:        measuring qualitative characteristics. Nijmegen Center for Economics , 9-17.Blesia, J. U., & Hutadjulu, L. Y. (2016). Factors That Affect The Perception of Small       and Medium-Sized Businesses (SMEs)? Community on The Importance of         Financial Statements, The Amount of Credit Received and Implementation    Prospects. KNE Publishing .Cassar, G. (2004). The financing of business start-ups. Journal of Business Venturing.DSAK. (2016). Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah.            Blog Universitas Indonesia.Eshima, Brian, Anderson, & Yoshihiro. (2011). The influence of firm age and        intangible resources on the relationship between entrepreneurial orientation        and firm growth among Japanese SMEs. Journal Business Venturing, 413-           429.Hendrian, Dwiyani, R., & Hadiwidjaja. (2016). Implementation of Accounting      Standard on Small and Medium-Sized Entities (SMEs). GATR Journals , 68- 78.IAI. (2016). Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah. IAI           Global.IASB. (2009). International Financial Reporting Standard for Small and Medium- sized Entities (IFRS for SMEs). London International Accounting Standards Board .IASB. (2009). International Financial Reporting Standard for Small and Medium- sized Entities. London International Accounting Standards Board.Karadag, & Hande. (2017). the Impact of Industry, Firm, Age and education Level on      Financial Managenment Performance in Small and Mediun-sized        Enterorises(SMEs); Evidance from Turkey. Journal of Entrepreneurship in         Emerging Economies , 300-314.Kirschenmann, & Norden. (2010). The Relation between Borrower Risk and Loan             Maturity in Small Business Lending, Working Paper. Small Business .Lukacs, E. (2005). The economic role of SMEs in world economy, especially in      Europe. European Integration Studies , 3-12.Mutua, M., & John. (2015). Effect Of Bookkeeping On The Growth Of Small And           Medium Enterprises In Chuka Town European. Journal of Business and       Social Sciences , 102-112.Nanyondo, & Mary. (2014). Quality of financial statements, information asymmetry,         perceived risk and access to finance by Ugandan SMEs. Inder Science .Otchere, & Aboagye, F. (2012). The International Financial Reporting Standard for           Small and Medium-sized Entities (IFRS for SMES) Suitability for small          businesses in Ghana. Emerald Insight Journal of financial Reporting and             Accounting , 190-214.President. (1995, december 26). Undang-Undang No. 9 Tahun 1995. Retrieved     January3,2018,from             http://www.sjdih.depkeu.go.id/fulltext/1995/9TAHUN~1995UU.htmSamujh, R. (2007). IFRS for SMEs: a New Zealand perspective. The University of             Waikato .Seghers, A., Manigart, S., & Vanacker, T. (2012). The impact of human and social             capital on entrepreneurs? knowledge of finance alternatives. Journal of Small Business Management , 63-86.Solomon, Dickson, & Weaver. (2008). Entrepreneurial selection and success: does             education matter? Journal of Small Business and Enterprise Development,         239-258.Undang-Undang No. 9 Tahun 1995, Tentang Usaha Kecil.Vagias, & Wade, M. (2006). Likert-Type Scale Response Anchors. Marquatte .